2023
DOI: 10.1101/2023.03.02.530769
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome biology and evolution of mating type loci in four cereal rust fungi

Abstract: Sex defining loci or chromosomes often contain large non-recombining regions. In Basidiomycota, two distinct gene loci confer mate compatibility. These loci encode for homeodomain (HD) transcription factors and pheromone receptor (PR)-ligand pairs. In some fungi these two loci are physically linked and give rise to large evolutionary strata with extensive recombination suppression. To date genome level mating type (MAT) loci analysis is lacking for obligate biotrophic basidiomycetes that depend on their host p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 170 publications
(492 reference statements)
3
10
0
Order By: Relevance
“…Pca HD locus alleles published by Luo et al (2024). There is one discrepancy between the bW5 allele between the studies in which the first 12 N-terminal amino acids of bW5 defined by Luo et al (2024) are not encoded in the haplotypes used to define bW5 in this study.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Pca HD locus alleles published by Luo et al (2024). There is one discrepancy between the bW5 allele between the studies in which the first 12 N-terminal amino acids of bW5 defined by Luo et al (2024) are not encoded in the haplotypes used to define bW5 in this study.…”
Section: Discussionmentioning
confidence: 65%
“…There is one discrepancy between the bW5 allele between the studies in which the first 12 N-terminal amino acids of bW5 defined by Luo et al (2024) are not encoded in the haplotypes used to define bW5 in this study. In addition, the ‘ bW8bE8 ’ allele pair reported by Luo et al (2024) was only found in a single isolate (90MN5B) that was not included in our pangenome.…”
Section: Discussionmentioning
confidence: 72%
“…In rust fungi, these are two unlinked loci, one contains pheromone precursors and receptors ( P/R ) and the other contains homeodomain ( HD ) transcription factors that closely linked via a short DNA sequence. The HD locus encodes bW-HD1 and bE-HD2 genes which are highly multiallelic in rust fungi (Luo et al 2024) and many Basidiomycota (Coelho et al 2017). These transcription factors form heterodimeric complexes between alleles and regulate cellular development during mating and the fungal life cycle (Coelho et al 2017; Cuomo et al 2017; Holden et al 2023; Wilson et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In other cases, the alleles no longer discriminate against self-fertilization or are not required for mating, leading to a bipolar or even unipolar mating-type [10]. So far, all characterized rust fungi are tetrapolar [18], although very little is known about the majority of rusts' mating-type loci.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the published genome assemblies of P. striiformis f. sp. tritici identifies two alleles of each Pst-bW-HD1 and Pst-bE-HD2 in each genome on chromosome 4, although these are not always present in the published assembly, and five distinct alleles of each Pst-bW-HD1 and Pst-bE-HD2 in total, with the P/R locus being on chromosome 9 [18]. It has been hypothesized that maintenance of a plurality of mating-types is evolutionarily unfavourable without selection pressure to maintain outcrossing in sexual reproduction [10,24,25].…”
Section: Introductionmentioning
confidence: 99%